2007
DOI: 10.1614/ws-06-121
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Contemporary and Historical Waterhemp (Amaranthus tuberculatus) Accessions to Glyphosate

Abstract: Anecdotal reports suggest waterhemp is becoming more difficult to control with glyphosate. Waterhemp accessions collected primarily in Illinois before 1996, in 1998 to 1999, and in 2003, were evaluated for differential responses to glyphosate treatment. The pre-1996 group consisted of 10 accessions, whereas the 1998 to 1999 and 2003 groups consisted of 45 accessions each. Plants 10 to 12 cm in height from each waterhemp accession were treated with 0 or 220 g ae ha−1glyphosate. Although shoot dry biomass 14 d a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This difference can be as much as twofold (Volenberg et al 2007 ), and it is questionable if a twofold difference in sensitivity is really great enough to consider one biotype resistant and another susceptible, particularly if the discriminating dose is less than the normal fi eld rate. The results from multiple studies show that every weed species will require its own dose rate and that there are no rules of thumb that can be applied.…”
Section: Discriminating Dose Screensmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference can be as much as twofold (Volenberg et al 2007 ), and it is questionable if a twofold difference in sensitivity is really great enough to consider one biotype resistant and another susceptible, particularly if the discriminating dose is less than the normal fi eld rate. The results from multiple studies show that every weed species will require its own dose rate and that there are no rules of thumb that can be applied.…”
Section: Discriminating Dose Screensmentioning
confidence: 99%
“…glyphosate, although all of the populations were controlled at 870 g ha − 1 (Volenberg et al 2007 ). Lambsquarters ( Chenopodium album L.) (Hite et al 2008 ), giant ragweed ( Ambrosia trifi da L.) (Westhoven et al 2008 ), fi eld bindweed ( Convolvulus arvensis L.) (DeGennaro and Weller 1984 ;Westwood et al 1997 ), and pitted morningglory ( Ipomoea lacunosa L.) (Stephenson et al 2007 ) populations have also shown variable response to glyphosate.…”
mentioning
confidence: 99%
“…Sauer var. tuberculatus (Sauer) Coastea & Tardif ] exhibits large within-accession variability in response to glyphosate (Volenberg et al 2007). It was shown that waterhemp plants with reduced sensitivity to glyphosate were present in fields prior to the extensive use of glyphosate in glyphosate-resistant crops.…”
Section: Resultsmentioning
confidence: 99%
“…While troublesome, glyphosate-resistant horseweed is primarily a problem at pre-plant before crop establishment. The emergence of glyphosate-resistant Palmer amaranth (Amaranthus palmeri) and water hemp (Amaranthus rudis, A. tuberculatus) have caused severe and welldocumented management problems for in-season weed management in cotton and soybeans (Culpepper et al 2008;Legleiter et al 2008, Legleiter et al, 2009Norsworthy et al, 2008a;Norsworthy et al 2008b;Patzoldt et al 2002;Steckel & Sprague, 2004a;Steckel & Sprague, 2004b;Steckel et al 2007;Steckel et al, 2008;Volenberg et al 2007). …”
Section: Glyphosate Resistancementioning
confidence: 99%